2010
DOI: 10.1053/j.gastro.2010.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Variants Associated With Histologic Features of Nonalcoholic Fatty Liver Disease

Abstract: Background & Aims-There is little data available from genome-wide association studies (GWAS) of liver histology in patients with non-alcoholic fatty liver disease (NAFLD). We conducted a pilot GWAS in patients with NAFLD, characterized by histology, who were enrolled in the NASH CRN Database Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
229
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(246 citation statements)
references
References 43 publications
5
229
2
3
Order By: Relevance
“…Recently several genetic factors such as patatin-like phospholipase 3 or apolipoprotein C3 have been characterized in NAFLD (Valenti et al, 2010;Petersen et al, 2010). Even genomewide association studies (GWASs) of liver histology in patients with non alcoholic fatty liver disease have been performed to estimate genetic susceptibility to NASH (Chalasani et al, 2010). However, these findings have to be validated.…”
Section: Genetic Prevalencementioning
confidence: 99%
“…Recently several genetic factors such as patatin-like phospholipase 3 or apolipoprotein C3 have been characterized in NAFLD (Valenti et al, 2010;Petersen et al, 2010). Even genomewide association studies (GWASs) of liver histology in patients with non alcoholic fatty liver disease have been performed to estimate genetic susceptibility to NASH (Chalasani et al, 2010). However, these findings have to be validated.…”
Section: Genetic Prevalencementioning
confidence: 99%
“…Although the K45R substitution was apparently not detrimental to the protein, rs11549147 was suggested to be involved in aberrant exon splicing. Chalasani et al 26 studied the association of histological features of nonalcoholic fatty liver disease with SNPs related to lipid metabolism. They found that the nonalcoholic fatty acid disease score was significantly related to rs2645424 of FDFT1, located in intron 7.…”
Section: Discussionmentioning
confidence: 99%
“…While studying environment and nutritional behavior remains challenging, the genetic role of the variants located on the genes PNPLA3 (22)(23)(24) and transmembrane 6 superfamily member 2 (TM6SF2) (25) has been shown to modify the risks of hepatic steatosis and fibrosis. In addition, GWAS has identified other genetic variants associated with features of hepatic histology in patients with NAFLD (26). In addition, serum miRNA expression has been shown to correlate with liver steatosis in a twin study with a heritable trait (27) and could also account for familial cirrhosis.…”
Section: Discussionmentioning
confidence: 99%